Product Heterogeneity and Cost Allocations in Contingent Trade Protection. (14th July 2014) - Kelly, Brian D.
Abstract The WTO allows members to impose contingent protection, including anti‐dumping duties, within agreed constraints. Anti‐dumping proceedings typically name a single captioned product but include large numbers of individual products within that caption. The inclusion of multiple products creates a variety of issues for both anti‐dumping and other contingent protection measures, issues that have been prominent in national actions and WTO dispute settlements, but have been largely ignored in research. This work focuses on the most important such area, the allocation of costs among products in anti‐dumping proceedings. We develop a comprehensive economic analysis for cost allocation issues, and couple it with the accounting tools that must be used for its implementation, to derive the first‐best allocation methods for anti‐dumping purposes. These results have direct relevance in other contingent trade contexts, such as injury determinations and subsidy pass‐through analysis.